Letter to editor: careful literature search and exact data extraction are milestones of a meta-analysis: the case of dairy consumption and hip fracture - Hanieh Malmir; Ahmad Esmaillzadeh (BMC, 2018)
Abstract In a recent issue of the BMC Public Health journal, Bian et al. described the results of an interesting meta-analysis on the association between dairy products consumption and risk of hip fracture. Although the results are important and valuable, some critical points should be noticed in the explanation of these findings. We prepared these critical points in a letter to the editor and hope to be an interest of you.